2012
DOI: 10.1097/prs.0b013e31824a2bbd
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Breast Reconstruction with the Anterior Approach Latissimus Dorsi Flap and Permanent Implants

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Universal goals in all forms of reconstructive surgery, however, should include, wherever possible, minimizing scars, shortening operative time, and decreasing hospital stay. 2327 This procedure has been described before 16,17 ; however, we hoped to describe clearly our personal technique that requires no endoscopic equipment and no patient repositioning and that can be performed using instruments available to all plastic surgeons around the world. This procedure enables us significant savings in operating time, with the reconstructive surgeon able to start operating with a second team after completion of the first side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal goals in all forms of reconstructive surgery, however, should include, wherever possible, minimizing scars, shortening operative time, and decreasing hospital stay. 2327 This procedure has been described before 16,17 ; however, we hoped to describe clearly our personal technique that requires no endoscopic equipment and no patient repositioning and that can be performed using instruments available to all plastic surgeons around the world. This procedure enables us significant savings in operating time, with the reconstructive surgeon able to start operating with a second team after completion of the first side.…”
Section: Discussionmentioning
confidence: 99%
“…This gives the security of fully vascularized coverage of the prosthesis in the event of skin necrosis. The scarless latissimus dorsi flap 16,17 can harvest a significant proportion of the latissimus dorsi using standard breast surgery instruments and without requiring endoscopic instrumentation. It has the added significant advantage of no donor scar.…”
mentioning
confidence: 99%
“…Bittar et al. also reported elevating the latissimus dorsi flap with an anterior approach successfully; however, their incision technique was different from ours ( 13 ).…”
Section: Discussionmentioning
confidence: 61%
“…Direct-toimplant reconstruction, however, requires confirmation of the symmetry between the reconstructed implant and the normal breast with the patient in the sitting position, as this cannot be achieved with the patient in the lateral position (12). Bittar et al also reported elevating the latissimus dorsi flap with an anterior approach successfully; however, their incision technique was different from ours (13).…”
Section: Discussionmentioning
confidence: 73%
“…Use of latissimus dorsi flap combined with implants has been used for breast reconstruction; this combination method is most useful for patients with large volume breasts [4]. Recently, latissimus dorsi flap elevation alone via anterior approach and use of permanent implants with breast reconstructive surgery has been reported and exhibited acceptable results [5]. This method minimizes the back or abdominal scarring.…”
Section: Discussionmentioning
confidence: 99%